Analisis Kinerja Kolom Pipih dan Kolom Konvensional pada Bangunan Bertingkat Rendah - Tersianus Rada Sakti; Remigildus Cornelis; Dolly W. Karels (Universitas Nusa Cendana, 2022)
Unconventional columns are very familiar in modern building construction because they impact the room's efficiency. Meanwhile, conventional columns affect the lack of efficiency in the room's functions. The performance analysis of the two types of columns used pushover analysis of the capacity spectrum method using ETABS v 16.1.0 software. The performance level results of the two types of columns in low-rise buildings are the same, which is Immediate Occupancy. The most significant maximum shearing force is at a low-rise building with an unconventional column with a maximum displacement on the east side of 160,00 mm. The smallest is a low-rise building with a conventional column in the east direction with maximum displacement on the Nort side of 90,11 mm. Thus, comparing the performance of the two types of columns can be concluded that conventional columns are stronger than unconventional columns.